Theophylline-regulated pyrolysis synthesis of nitrogen-doped carbon nanotubes with iron-cobalt nanoparticles for greatly boosting oxygen reduction reaction - Zhang, Wei; Chen, Yu-Ping; Zhang, Lu; Feng, Jiu-Ju; Li, Xin-Sheng; Wang, Ai-Jun (Journal of colloid and interface science, 2022)
[Display omitted] At present, construction of economical, efficient and stable electrocatalysts for oxygen reduction reaction (ORR) is critical to alleviate the energy shortage. Theophylline (THP) can be easily extracted from natural plants, whose nitrogen atoms can chelate with metal ions. With assistance of THP, FeCo alloy was confined in N-doped carbon nanotubes (FeCo/NCNTs-800) by one-step pyrolysis of a mixture of the metal precursors, g-C3N4 and THP. The resulting FeCo/NCNTs-800 showed a better ORR performance (onset potential, Eonset = 1.09 V; half-wave potential, E1/2 = 0.87 V) than commercial Pt/C (50 wt%) in a 0.1 M KOH solution, with a limiting current density as high as –5.54 mA cm−2. This work offers a feasible strategy for developing transitional bimetal-based carbon catalysts in alkaline fuel cells.